Oportunidades e desafios para a implementação das equipes de investigação de alto desempenho na polícia federal - Amorim, Fernando (2019)
As in the other investigative police agencies, little has been discussed, in the Brazilian Federal Police, about more modern forms of work organization such as high performance teams. For this purpose, a research was carried out at the Brazilian Federal Police specialized unit for patrimonial crimes and the arms trafficking located in the state of Espírito Santo, where three investigations were conducted by a police team formed from the high performance teams model of work organization. A qualitative approach was adopted, opting for the action-research method. The team, formed by one police chief, one clerk and two agents, corresponds to the standard formation of a team in the Federal Police. The data collection took place from the recording and subsequent transcription of the team meetings and recording of the communication the team performed through a specific group created in a instant messaging application. As a result, a qualitative improvement was detected in the investigation, since each police officer participated in the definition of the investigative line and had remote access to the other relevant information added to the investigation. However, it has not been possible to state that the high-performance team model leads to a faster investigation. Based on the results of the research, a model of implementation of the high performance teams in the police investigation was developed, based on two pillars: the investigation and discussion meetings for the initiation of the investigation and the carrying out of sensitive investigations; and the online investigation dossier